Is laparoscopic resection of hepatocellular carcinoma feasible? - Djokić, Mihajlo (Surgery and surgical endoscopy, 2019)
Background. Hepatocellular carcinoma is the most common carcinoma of the liver. Its treatment depends on the number of lesions, state of liver parenchyma, systemic liver function, presence of portal hypertension, and esophageal varices as well as the patient%s other concurrent diseases. Mortality and comorbidity are associated with the state of liver parenchyma and the liver function, which is assessed by the Child%Pugh score, and further treatment is decided based on the Barcelona Clinic Liver Cancer classification. Methods. The advantages and disadvantages of laparoscopic resection of hepatocellular carcinoma are discussed in the article, and the results of these procedures at the Ljubljana University Medical Center are reviewed. Results. Between 2012 and 2017, 21 laparoscopic resections of hepatocellular carcinoma were performed at the Ljubljana University Medical Center. All patients were stage 0 or A carcinoma according to the Barcelona Clinic Liver Cancer classification (T1 or T2 on TNM score). In five patients a conversion to open resection was required due to hemorrhage, insufficient visibility, extensive adhesions, and previously undiagnosed satellite hepatocellular carcinoma lesion. The laparoscopic resection compared to classic resection resulted in shorter hospitalization time (in average 7.3 days), lower incidence of complications (6.25%), or less progress of the disease (18.75%). All resections were R0 and all patients survived. Conclusion. The laparoscopic resection of hepatocellular carcinoma is feasible in appropriately selected patients in the hands of an experienced surgeon.
Keywords: hepatocelularni karcinom; jetra; karcinom; laparoskpopska kirurgija